The Importance of Implementing E-HRM to Enhance Employee Productivity in Companies - Evi Silvana Muchsinati; Rano Ardiansyah (Asian Journal of Management, Entrepreneurship and Social Science, 2023)
The purpose of this study was to learn how much of an impact E-Human Resource Management (E-HRM) had on productivity in Batam's industrial firms. In today's era of increased globalization, businesses of all sizes are scrambling to adopt E-HRM systems that make use of the cutting-edge technologies of Industry 4.0 in order to stay competitive. These results were processed using the statistical packages Statistical Package for the Social Sciences (SPSS) and SmartPLS 3 (Partial Least Squares). Three Batam-based manufacturing firms, PT. OSI Electronics Batam, PT. Sat Nusapersada, Tbk, and PT. Sumitomo Indonesia, which use E-HRM, provided the 402 participants for this study. One interesting aspect of this study is the mediation role played by the innovation variable. The effects of E-Communication on innovation and two mediation hypotheses were the only ones to fail testing out of a total of 11. Therefore, it is safe to say that E-HRM has been shown to increase output in Batam's manufacturing firms.